Effect of CREB1 promoter non-CpG island methylation on its differential expression profile on sheep ovaries associated with prolificacy. (June 2019) - Zhao, Jie; Li, Feng-zhe; Wu, Jie; Yang, Hua; Zheng, Jian; Pang, Jing; Meng, Fan-xing; Wang, Feng; Zhang, Yan-li
Highlights: CREB1 was expressed in granulosa cells and theca cells of mature follicles. Methylation of DMR of promoter were increased in HP group than that in LP group. The non-CGI methylation of CREB1 promoter may regulate gene expression on sheep ovaries. Abstract: This study aimed to investigate the effect of different methylated regions of cyclic-AMP response element binding protein 1 (CREB1) by comparing the high prolificacy (HP) group and low prolificacy (LP) group, which was detected in our previous study. The expression level of CREB1 mRNA in the ovaries of the HP group was higher than in the LP group ( P < 0.05). The differential methylated region (DMR) had 4 methylated CG dinucleotides(CGs): −1546, −1544, −1494 and −1464. The DNA methylation levels of -1546 CGs and −1464 CGs were significantly higher in the HP group than in the LP group ( P < 0.05). The activity from −1296 to +26 (without DMR) was significantly higher than the activity from −1598 to +26 (with DMR) ( P < 0.05). The result of 5-aza-2′-deoxycytidine treatment indicated that the inhibition DNA methylation of DMR reduced the transcription of CREB1. The bioinformatics predictive analysis were found that the −1546 CG site was located in the CCAAT/enhancer-binding protein alpha (CEBPA) binding site and the -1464 CG site was located in the Sp1 binding site. Finally, this study revealed the relationship between the methylation of non-CpG sites of the promoter and transcription of CREB1. This study will provide a theoretical basis of the Hu sheep ovaries associated with DNA methylation.